THE EFFECT OF PROFITABILITY, LEVERAGE AND GROWTH OPPORTUNITY ON PROPERTY AND REAL ESTATE COMPANY VALUE IN 2014-2019 - Avialda, Ratih; Muslihat, Asep (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This research aims to find out, analyze, and explain the effect of profitability, leverage, and growth opportunity on the firm value of property and real estate companies listed on the Indonesia Stock Exchange in 2014-2019. In this research, the authors utilize ROA, DER, and growth total assets as proxies of each variable profitability, leverage, and growth opportunity, as well as PBV as proxies of the firm value. The research sample of 20 companies was obtained from a purposive sampling technique. Data analysis techniques are performed with the help of the SPSS 25 program consisting of descriptive statistics analysis and multiple linear regression analysis, as well as hypothesis testing as verificative analysis. Based on hypothetical test results, partial profitability and leverage have a significant positive effect on the firm value, while the growth opportunity has no significant effect on the firm value. Simultaneously profitability, leverage, and growth opportunity had a significant positive effect on the firm value with an influence of 44.40% and 55.60% influenced by other variables outside of this study.